Occupational Health Hazards among Women Fish Vendors in Thiruvananthapuram, Kerala - Vijayan, B Kavya; Vijayakumari, Sithara Balan (Indian Journal of Extension Education, 2025)
The informal sector constitutes a significant source of employment for women in India, particularly in coastal regions such as Kerala, where fish vending serves as a primary livelihood, and women frequently encounter substantial occupational health risks stemming from extended working hours and inadequate ergonomic conditions. The study aims to examine the multifaceted occupational health hazards affecting women fish vendors in Thiruvananthapuram district, carried out during 2025, with a particular emphasis on physical, reproductive, and psychosocial health dimensions. Data were collected from a sample of 150 women fish vendors through structured interviews, observational checklists, and a quality of life rating scale. The findings revealed a high incidence of musculoskeletal disorders, fatigue, dermatological conditions, and reproductive health concerns among the women fish vendors. Significant correlations were observed between health status and factors such as education level, household dependency ratio, income, and housing type. The study underscores the critical need for targeted policy interventions, comprehensive health education, infrastructural enhancements, and gender-sensitive occupational safety protocols to safeguard the health and dignity of women engaged in the unorganised sector.
Keywords: Occupational health hazard; Reproductive health; Informal sector; Fish vendors; Fisher women; Quality of life